Solvothermal Synthesis and Characterization of Indium Oxid Nanoparticles - Rasheed, Rashed T.; Al-Algawi, Saryia D.; Jaffer, Layla A. (Iraqi Journal of Science, 2022)
In this study, In2O3 was prepared by Solvothermal technique in autoclave device, which is a simple and inexpensive technique to indicate the best condition. The reaction took place between indium chloride and urea. In(OH)3 as-prepared annealing at 100°C and convert to In2O3 at annealing temperatures 300, 500, 700 °C for 90 min .The physical properties of nanoparticles were characterized by XRD, SEM, AFM, UV/Visible and FTIR spectroscopy measurements. The examination results of XRD for In2O3 powder annealed at different temperature showed the formation of a cubic phase of nanoparticles with high intensity of plane (222). The lattice constant decreases with the increase of annealing temperature (from 10.07 to 10.04 Ǻ). AFM indicated an increase in grain size of In2O3 with increasing of annealing temperatures (from 78.59 to 94.4 nm). The optical properties, transmittance of In2O3 nanoparticles at annealing temperatures 500°C have a high transparent reach to (89%) and Energy gap Increases with increasing annealing temperature in range (3.6 to 4.65 eV).